Exploring the Influence of Various Solvents on the Structural, Optical, and Spectroscopic Properties of MgO - Mohammed, Bast Ahmed; Kareem, Rebaz Obaid; Bulut, Niyazi; Demirci, Tuna; Elibol, Erdem; Ercan, Filiz; Kaygili, Omer (TUBITAK, 2024)
Magnesium oxide (MgO) samples were manufactured at different temperatures using various solvents of water and ethanol. MgO structure was also modeled and its vibration modes were calculated. The kind of solvent as-used in the synthesis and calcination temperature caused changes in the lattice parameter, crystallinity, and crystallite size. The crystallite size increased with increasing production temperature for both series of the MgO. The morphology and bandgap energy were also affected significantly by the solvent and calcination temperature. © 2024, TUBITAK. All rights reserved.
Keywords: Bandgap energy; MgO